Guidance and navigation of a wheeled mobile robot - Goh, Ing Jya. (2009)
This project is a continuation of the works of many past graduating students. The scope of this line of endeavor revolves around the development of an autonomously driven four-wheeled vehicle. The long term goal is to produce a small autonomous mobile robot suitable for the role of a passenger agent in a marsupial robotic team. The objective of this project is to further refine and develop the navigational capability of the handed-down four-wheeled vehicle. The scope of work involves the development of a simple mapping algorithm suitable for application in a simple enclosed rectilinear environment. Changes to the mobile robot include the incorporation of a high resolution digital fluxgate compass and the replacement of the original set of onboard stepper motors. Asynchronous communication channels are established between the onboard processors to facilitate the transferring of data and a half-duplex wireless platform is set up to allow non-local control of the mobile robot from a remote computer. The mobile robot is subjected to a series of experiments and tests to calibrate its odometric accuracy. The revamped mobile robot demonstrated improved accuracy in odometry and obstacle detection. The robot also exhibited the ability to communicate wirelessly.